Expansion of Base Station Coverage Area Based on Sector Expansion on Lombok Island - Kelvin, Kelvin; Fat, Joni; Hugeng, Hugeng (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2025)
Developing telecommunications infrastructure is vital for national advancement, improving connectivity to accelerate information flow and access to public services. Effective base station planning prioritizes maximizing network coverage in densely populated areas. However, traditional visualization methods often fall short in identifying regions with the highest population density. This study addresses this gap by applying a sector expansion algorithm to select optimal base station locations within the most densely populated sectors, achieving more balanced network coverage. Using Indonesia's population data and administrative boundaries, optimal base station locations are determined with DBSCAN and K-Means clustering algorithms. The network's reach is then enhanced through sector expansion to increase coverage in areas with high population density by selecting new base station locations based on the densest sector around a primary station. The candidate station is positioned at a distance of three-quarters of twice the radius of the primary station, optimizing coverage while remaining close to existing network resources. The evaluation compares population coverage before and after sector expansion, assessing connectivity between base stations and distribution efficiency. Results show that sector expansion increased population coverage on Lombok Island from 15.94% to 99.14%, with the most populated base station covering up to 34,274 people, enhancing distribution efficiency.